Merdeka Curriculum Management in Strengthening the Pancasila Student Profile - Atik Widiyawati; Rasiman; Endang Wuryandini (Newinera Publisher, 2026)
This study aims to analyze the management of the Merdeka Curriculum in strengthening the Pancasila Student Profile at H Moenadi State Vocational School. Employing a qualitative approach with a case study design, the research involved key stakeholders, including the principal, vice principal for curriculum, teachers, students, and parents. Data were collected through in-depth interviews, direct observations, and document analysis, and were analyzed using thematic analysis. The findings indicate that the implementation of the Merdeka Curriculum has been carried out relatively well across the stages of planning, implementation, and evaluation. Teachers generally understand the curriculum as a flexible and student-centered framework and have integrated project-based learning through the Project for Strengthening the Pancasila Student Profile (P5) to foster students’ character and 21st-century skills. The results also reveal positive impacts on students’ cooperation, independence, creativity, critical reasoning, and self-confidence. However, challenges remain in the form of variations in teacher readiness, administrative workload, limited instructional time, and inconsistent reflective documentation. The study concludes that effective curriculum management, supported by continuous professional development, structured collaboration, and systematic evaluation, is essential to ensure the sustainability and quality of Merdeka Curriculum implementation in vocational education.